Proceedings of the 23rd ACM International Conference on Multimedia 2015
DOI: 10.1145/2733373.2806262
|View full text |Cite
|
Sign up to set email alerts
|

Gradient-based 2D-to-3D Conversion for Soccer Videos

Abstract: A wide spread adoption of 3D videos and technologies is hindered by the lack of high-quality 3D content. One promising solution to address this problem is to use automated 2D-to-3D conversion. However, current conversion methods, while general, produce low-quality results with artifacts that are not acceptable to many viewers. We address this problem by showing how to construct a high-quality, domainspecific conversion method for soccer videos. We propose a novel, data-driven method that generates stereoscopic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Recent works [61,60,43,59] have shown that, for some domains, data derived from video games can significantly reduce manual labor and labeling, since ground-truth labels can be extracted automatically while playing the game. E.g., [15,59] collected depth maps of soccer players by playing the FIFA soccer video game, showing generalization to images of real games. Those works, however, focused on low level vision data, e.g., optical flow and depth maps rather than full high quality meshes.…”
Section: Related Workmentioning
confidence: 99%
“…Recent works [61,60,43,59] have shown that, for some domains, data derived from video games can significantly reduce manual labor and labeling, since ground-truth labels can be extracted automatically while playing the game. E.g., [15,59] collected depth maps of soccer players by playing the FIFA soccer video game, showing generalization to images of real games. Those works, however, focused on low level vision data, e.g., optical flow and depth maps rather than full high quality meshes.…”
Section: Related Workmentioning
confidence: 99%